Pengembangan Desain Busana Pesta Muslim Maskulin Dengan Inspirasi Pinecone - Cisadewi, Lea; Yulistiana, Yulistiana (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
The purpose of the study was to determine the development of masculine muslim party dress designs with Pinecone inspiration. Inspired by the Pinecone which can open its scales when it's dry and close its scales when it's cold. Method used is the Double Diamond Design Process which consists of 4 stages: Discover stage by searching and gathering information about Pinecone. Define stage is the identify stage from the Discover and determines the most important priorities which are combined on the Moodboard and handling order. Develop stage is the design development stage from the basic design to be transformed into a masculine muslim party dress in the form of an A-line silhouette dress, there is a long waistcoat, the colors used are monochromatic colors, and application of decorative motifs with embroidery and laser cutting techniques. Deliver stage is the last stage, input is collected, selected, and approved with the 5 best design developments and the most appropriate sources of inspiration in the form of two-piece and three-piece clothing. Results showed that to make appropriate masculine muslim party dress, it is necessary to develop a design so that new innovations in masculine muslim party dress will emerge.